Pengaruh Keterampilan Interpersonal,Teknologi Informasi dan Komunikasi, Serta Partisipasi Masyarakat Terhadap Kinerja Melalui Tata Kelola Badan Usaha Milik Desa di Kabupaten Semarang - Destiya Wahyu Ananda Putri; Dhian Andanarini Minar Savitri (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The purpose of this study is to determine whether Village-Owned Enterprise Governance mediates the influence of Interpersonal Skills, Information and Communication Technology on Performance, and Community Participation on performance. The method used in this study is quantitative, the data used is primary data. The number of respondents used is 73 respondents. The sampling technique is purposive sampling. The data analysis technique used is multiple regression analysis and Sobel Test. The results found in this study are Interpersonal Skills and Information and Communication Technology do not affect Performance. Community Participation has a significant effect on Performance. Village-Owned Enterprise Governance as a mediation variable does not affect Performance. Village-Owned Enterprise Governance are able to mediate Interpersonal Skills and Information and Communication Technology on Performance. Village-Owned Enterprise Governance is not able to mediate Community Participation on Performance.